Volatile constituents of the fruit oil of pittosporum spp. - Dato’yaacob, Karim; Ariffin, Saleha (Taylor & Francis, 2000)
An expressed oil of the fruit of Pittosporum spp. was analyzed by GC and GC/MS. Fifteen compounds were identified in the oil, of which α-pinene (60.2%) was the major component. Chiral GC analysis revealed that α-pinene was made up of more than 99% (R)-enantiomer.